Determination of Job Stress among Nurses in Cardiac Surgical Intensive Care Units in Baghdad City - Bayda'a A. Kareem (Iraqi National Journal of Nursing Specialties, 2023)
Objective: The study aimed to determine the sources and level of job stress experienced by nurses who wereworking in intensive care units, and to find-out the relationship between work-related stress and some variablessuch as age, gender, educational level, marital status, and years of experience in cardiac surgical intensive careunit.Metl]odo]ogy: A descriptive study was conducted on nurses working in the cardiosurgical intensive care units inBaghdad hospitals. The study sample was selected purposively and consisted of (60) nurses who were workingin cardiosurgical intensive care units in Baghdad city (Ibm Al-Betar Hospital for Cardiac Surgery, Ibn A1-NafisHospital for Cardiovascular Diseases, and the Iraqi Center for Heatt Diseases) for the period of February l§t2006 to April 6th 2006. Interview technique was employed and each interview took approxinately 20-30 minuetswhen the nurse filled the questionnaire. A questionliaire was designed by the investigators which consisted oftwo parts, first pat is concerned with the demographic characteristics of the sample and the second one isconcerned with the environmental stressors, and it contains (28) items that describes the physical andpsychological stressors .Results: The results of the study revealed that most of the sample was female, their ages ranged from (30-39)years, university graduates, single, duration working in cardiosurgical intensive care units for (6-10) years. Also,the results revealed that nurses in cardiac surgical intensive care units suffering from severe level of stress in theareas of physical and psychological, and the physical stressors had more severity.Recommendations: The recommends that stress management programs should be employed to assistcardiosurgical intensive care units nurses to deal with job stress and providing training opportunity for them is avital process to meet the new challenges.